Organic amendment additions to rangelands: A meta‐analysis of multiple ecosystem outcomes. (2nd January 2019) - Gravuer, Kelly; Gennet, Sasha; Throop, Heather L.
Abstract: Interest in land application of organic amendments—such as biosolids, composts, and manures—is growing due to their potential to increase soil carbon and help mitigate climate change, as well as to support soil health and regenerative agriculture. While organic amendments are predominantly applied to croplands, their application is increasingly proposed on relatively arid rangelands that do not typically receive fertilizers or other inputs, creating unique concerns for outcomes such as native plant diversity and water quality. To maximize environmental benefits and minimize potential harms, we must understand how soil, water, and plant communities respond to particular amendments and site conditions. We conducted a global meta‐analysis of 92 studies in which organic amendments had been added to arid, semiarid, or Mediterranean rangelands. We found that organic amendments, on average, provide some environmental benefits (increased soil carbon, soil water holding capacity, aboveground net primary productivity, and plant tissue nitrogen; decreased runoff quantity), as well as some environmental harms (increased concentrations of soil lead, runoff nitrate, and runoff phosphorus; increased soil CO2 emissions). Published data were inadequate to fully assess impacts to native plant communities. In our models, adding higher amounts of amendment benefitted four outcomes and harmed two outcomes, whereas adding amendments with higher nitrogen concentrations benefitted two outcomes and harmed four outcomes. This suggests that trade‐offs among outcomes are inevitable; however, applying low‐N amendments was consistent with both maximizing benefits and minimizing harms. Short study time frames (median 1–2 years), limited geographic scope, and, for some outcomes, few published studies limit longer‐term inferences from these models. Nevertheless, they provide a starting point to develop site‐specific amendment application strategies aimed toward realizing the potential of this practice to contribute to climate change mitigation while minimizing negative impacts on other environmental goals. Abstract : On rangelands, application of organic amendments such as compost and biosolids is increasingly proposed for climate change mitigation. Considering a range of ecosystem outcomes, this meta‐analysis found that organic amendments, on average, provide some environmental benefits (increased soil carbon, soil water holding capacity, aboveground net primary productivity, and plant tissue nitrogen; decreased runoff quantity), as well as some environmental harms (increased concentrations of soil lead, runoff nitrate, and runoff phosphorus; increased soil CO2 emissions). Our models can be used to design site‐specific amendment application strategies, helping to realize the potential benefits of this practice while minimizing environmental harms.